Impact of Militarization and Economic Growth on Biofuels Consumption and CO2 Emissions: The Evidence From Brazil, China, and US - Bildirici, Melike (WILEY, 2018)
The relation among CO2 emissions, economic growth, militarization, and biofuel consumption were analyzed from 1985 to 2015 period for Brazil, China, and US. It was used to The Autoregressive Distributed lag and three supplementary long-run estimators: the Dynamic OLS, Canonical Cointegration Regression, and Fully Modified OLS to reveal the long run impacts between variables. Toda and Yamamoto's MWALD and Rao F tests were applied to find out the direction of causality. The evidence of bidirectional causality between biofuel consumption and economic growth, between economic growth and CO2 emissions was determined. The results of forecast-error variance determined 25% of FEV of biofuel consumption is explained by CO2 emissions, while around 51% of the FEV of CO2 emissions is explained by the FEV of militarization in China and US, and 31% in Brazil. (C) 2017 American Institute of Chemical Engineers
Keywords: biodiesel; biomass; CO2; energy policy; environmental policy; BIOMASS ENERGY-CONSUMPTION; STATISTICAL-INFERENCE; ECOLOGICAL FOOTPRINTS; I(1) PROCESSES; FRESH EVIDENCE; UNITED-STATES; SOUTH-AFRICA; REGRESSIONS; ENVIRONMENT; MILITARY; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology